The Transformation of Islamic Education Values in the Symbolism of the Kembar mayang on the Javanese Wedding Tradition - M. Abdillah Subhin (Jurnal Pendidikan Nusantara, 2025)
This study aims to interpret the symbolism of twins in Javanese marriage traditions and uncover their relevance to Islamic education. Kembar mayang, which is traditionally interpreted as a symbol of harmony, fertility, and balance, is often seen only as a traditional ornament. Previous research tends to stop at anthropological studies without attributing this symbolism to Islamic education. Through a qualitative approach with a hermeneutical ethnography, this study explores data from PAI teachers, scholars, traditional leaders, communities, and students in Tulungagung with interview, observation, and documentation techniques. Data analysis was carried out using the Miles & Huberman model combined with Paul Ricoeur's hermeneutics. The results of the study found that the mayang twins are still preserved in about 65% of Javanese traditional wedding processions and are understood by the community as an Islamic prayer that includes the values of monotheism, morality, gratitude, tazkiyah al-nafs, and ukhuwah. PAI teachers use it as a medium for moral learning, scholars interpret it as family prayers of sakinah, mawaddah, wa rahmah, while the community makes it a means of strengthening friendship. Thus, twins can be transformed into Islamic educational instruments based on local wisdom. In conclusion, the symbolism of the twins is not just a cultural heritage, but a living text that can be reinterpreted with Ricoeur's hermeneutics and Al-Ghazali's moral ethics. This research presents novelty by offering a model of integration of Javanese cultural traditions and Islamic education that is relevant for the formation of the character of the Javanese Muslim generation in the modern era.